Information and Communication Technology Literacy of Public Elementary School Teachers - Montes, Gil (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the Information and Communication Technology (ICT) literacy of public elementary school teachers in Taytay II District, Schools Division Office of Rizal during School Year 2025–2026. The study employed descriptive survey research design and documentary analysis involving 337 teachers, representing 50 percent of the total population of 674 teachers from selected elementary schools in the district. Respondents were profiled according to age, sex, civil status, position, educational attainment, length of service, and in-service trainings attended. A researcher-made questionnaire checklist and documentary analysis of Individual Performance Commitment and Review (IPCR) ratings were utilized. Findings revealed that teachers were mostly female, married, and aged 31 years and above, with majority pursuing graduate studies, holding Teacher I positions, and having more than 10 years of experience with multiple in-service trainings. Results showed that teachers were much literate in ICT in terms of technological competence, pedagogical competence, and digital citizenship. There was no significant difference in ICT literacy in terms of sex, civil status, and position, while significant differences were found in age, educational attainment, length of service, and trainings attended. Teachers demonstrated very satisfactory performance based on IPCR ratings, and a significant relationship was found between ICT literacy and work performance. Age, educational attainment, length of service, and training attendance were identified as significant predictors of ICT literacy and performance. Teachers occasionally encountered problems in the utilization of ICT tools in teaching and learning. It is recommended that continuous ICT training, provision of adequate digital resources, and implementation of the proposed action plan be prioritized to enhance teachers’ ICT literacy and performance. Overall, the study underscores ICT integration as essential in improving instructional delivery and suggests sustained professional development and institutional support to ensure effective teaching, learning innovation, and improved educational outcomes in public elementary schools across the district level context.
Keywords: ICT literacy, technological competence, pedagogical competence, digital citizenship, public elementary school teachers, instructional performance, Taytay II District